2020
DOI: 10.1002/hbm.25094
|View full text |Cite
|
Sign up to set email alerts
|

Decoding attention control and selection in visual spatial attention

Abstract: Event‐related potentials (ERPs) are used extensively to investigate the neural mechanisms of attention control and selection. The univariate ERP approach, however, has left important questions inadequately answered. We addressed two questions by applying multivariate pattern classification to multichannel ERPs in two cued visual spatial attention experiments (N = 56): (a) impact of cueing strategies (instructional vs. probabilistic) on attention control and selection and (b) neural and behavioral effects of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…However, the univariate analysis could not fully explain variability in behavior and deficits in complex and subtle neural processing of selective attention. Consistent with previous studies (Bae & Luck, 2018 ; Bae & Luck, 2019 ; Hong et al, 2020 ; Li et al, 2022 ), through machine learning of multichannel ERP signals, the ability of children with ADHD to represent the target spatial location was significantly worse than the target localization ability of TD children. In addition, a delayed peak latency of decoding accuracy in children with ADHD revealed slower target detection during a visual search.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the univariate analysis could not fully explain variability in behavior and deficits in complex and subtle neural processing of selective attention. Consistent with previous studies (Bae & Luck, 2018 ; Bae & Luck, 2019 ; Hong et al, 2020 ; Li et al, 2022 ), through machine learning of multichannel ERP signals, the ability of children with ADHD to represent the target spatial location was significantly worse than the target localization ability of TD children. In addition, a delayed peak latency of decoding accuracy in children with ADHD revealed slower target detection during a visual search.…”
Section: Discussionsupporting
confidence: 88%
“…We applied a recently proposed multivariate pattern decoding approach (Bae & Luck, 2019 ; Hong et al, 2020 ; Li et al, 2022 ) to classify the target locations (Figure 2 ). Decoding was considered correct only if the classifier correctly determined the target location, and chance performance was therefore 25%.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, physical activity seems to be related to relying more on cues for engaging anticipatory attentional control, reflected in both behavioral measures (reaction time difference between uncued vs. cued targets) and brain measures (anticipatory interhemispheric asymmetry of alpha oscillations). Indeed, earlier studies have indicated individual differences in the adherence to the cue and its subsequent effect in target processing and the ultimate behavioral performance (Hong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons for such divergences are that language control is not an allor-none phenomenon; rather, it is more likely to be a continuum. Recently, MVPA has been adopted to effectively decode EEG data associated with cognitive processes such as working memory (Bae & Luck, 2018 and visual spatial attention (Hong et al, 2020). Specifically, taking spatial configuration into consideration, fine-grained information presented in the scalp distribution of EEG signals can be detected instead of temporal information over single electrodes in the traditional univariate component analysis (Bae & Luck, 2018.…”
Section: Bilingual Language Switching and Language Controlmentioning
confidence: 99%